Validation of the Chinese version of the physical education teacher job satisfaction scale - Yuan, Junfeng; Zhang, Liping; Weng, Shaojing; Yin, Yujia; Li, Chen; Luo, Lin (Frontiers in Psychology, 2022)
Purpose:The purpose of this study was to test the factor structure as well as the reliability of the Physical Education Teacher Job Satisfaction Scale (PETJSS). Method:The scale's structural validity, internal consistency and reliability were examined using CFA and Cronbach alpha. The predictive validity of the PETJSS was examined using Teacher Self-Efficacy (TSES-11) and the personal characteristics of the subjects. Result:The three-factor structure of the PETJSS was confirmed.The PETJSS three-dimensional model had good internal consistency/reliability.The three dimensions of the PETJSS (colleague satisfaction, parent satisfaction and student behaviour satisfaction) explained 81.206% of the overall job satisfaction . Also, the PETJSS demonstrated the expected correlation with teachers' self-efficacy, while the PETJSS test results were related to physical education teachers' job titles. Conclusion:The PETJSS (Chinese version) can be considered as a valid and reliable method.